Usaha Dakwah Nur al-Din al-Raniri Menentang Kesesatan Kaum Wujudiyyah dalam Kitab Ma`a al-Hayah li Ahl al-Mamat - Aini, Zulkefli; Sa’ari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
The article presents a brief exposition on Nur al-Din al-Raniri refutation of Acehnese wujudiyyah group’s mystical philosophy based on his work namely Ma`a al-Hayah Li Ahl al-Mamat. Through this particular writing, al-Raniri who was born in Ranir, India, demonstrated his vigorous effort to reform Islamic life and practice among the Acehnese especially in a polemic against the type of the ‘heretical’ wujudiyyah. Al-Raniri’s refutation of wujudiyyah’s teaching which he considered “heretical’ and which he used as evidence for branding that particular group with infidelity, according to his work, were based upon several points such as the issues of wahdah al-wujud, the relations between God and His creation, the relations between Shari`ah and Haqiqah, and the issues of Shatahat. Based on his significant role in this field, he is regarded as the first man of Muslim preacher (da`i) in the Malay world to clarify the distinction between the truth and the false interpretation on the doctrine of wujudiyyah arised in archipelago society.